2009
DOI: 10.1002/stem.102
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific T-Cell Response from Dendritic Cell Vaccination Using Cancer Stem-Like Cell-Associated Antigens

Abstract: Glioblastoma multiforme is the most aggressive primary brain tumor, with current treatment remaining palliative. Immunotherapies harness the body’s own immune system to target cancers and could overcome the limitations of conventional treatments. One active immunotherapy strategy uses dendritic cell (DC)-based vaccination to initiate T cell-mediated anti-tumor immunity. It has been proposed that cancer stem-like cells (CSCs) may play a key role in cancer initiation, progression and resistance to current treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
131
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(143 citation statements)
references
References 25 publications
8
131
0
2
Order By: Relevance
“…[37][38][39][40] However, the mechanisms involved have yet to be fully defined and no experimental evidence has been provided for direct targeting of CSCs by CSC-DC vaccine-induced anti-CSC immunity. We report herein that the therapeutic efficacy of our CSC-DC vaccine was associated with significantly inhibited metastasis to the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40] However, the mechanisms involved have yet to be fully defined and no experimental evidence has been provided for direct targeting of CSCs by CSC-DC vaccine-induced anti-CSC immunity. We report herein that the therapeutic efficacy of our CSC-DC vaccine was associated with significantly inhibited metastasis to the lung.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies in these regards, while limited, have focused on cellular immunity, e.g., higher production of interferon g (IFNg) by T cells, 40 or enhanced tumor infiltration of CD8…”
Section: Discussionmentioning
confidence: 99%
“…This may be of particular relevance for DFTD, where vaccination strategies have been proposed as a method of halting the devastating spread and extinction threat [2,9], while similar approaches are being evaluated for CTVT [45]. Although investigational, data suggest that for some tumors the CSC component represents a particular target for vaccine-based therapy [46][47][48]; as such, identification of a putative CSC for these tumors may be helpful.…”
Section: Discussion and Possible Utility Of A Csc Approachmentioning
confidence: 99%
“…Cancer antigens could be loaded onto DCs by nano-sized carriers including nanoparticles or nanoemulsions (Park et al, 2013). Studies on mice have shown DCs primed by CSCs antigens effectively induced immune response to tumor cells and prolonged survival (Lu et al, 2015;Ning et al, 2012;Xu et al, 2009). Treatment with DCs loaded with CSCs-derived antigen induced a tumorspecific immune response stronger than that induced by DCs loaded with normal tumor cells (Dillman et al, 2012;Jachetti et al, 2013).…”
Section: Cancersmentioning
confidence: 99%